1997
DOI: 10.1126/science.277.5326.693
|View full text |Cite
|
Sign up to set email alerts
|

A Cytoplasmic Inhibitor of the JNK Signal Transduction Pathway

Abstract: deviation from topological equilibrium for relaxation predicted by the model agrees with our experimental results and provides an explanation for the puzzling observation that type II topoisomerases are much better at decatenation and unknotting than relaxation (10,13,14).The ability of type II topoisomerases to directionally simplify DNA topology is in accord with their physiological role in DNA replication and chromosome segregation (25). Every turn of the double helix that is replicated introduces a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
607
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(638 citation statements)
references
References 31 publications
28
607
0
3
Order By: Relevance
“…Such transfer is obviously impaired in our tumor cell lines, because we detect inhibitor-containing cyclin E-cdk2 complexes in the cytoplasm. Cyclin E-cdk2(-inhibitor) complexes in transformed cells could be associated with a protein that causes cytoplasmic retention was recently shown for JIP-1 associated JNK (Dickens et al, 1997). A cytoplasmic retention signal can be dominant over the NLS as is the case with cyclin B-cdc2 complexes (Pines and Hunter, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…Such transfer is obviously impaired in our tumor cell lines, because we detect inhibitor-containing cyclin E-cdk2 complexes in the cytoplasm. Cyclin E-cdk2(-inhibitor) complexes in transformed cells could be associated with a protein that causes cytoplasmic retention was recently shown for JIP-1 associated JNK (Dickens et al, 1997). A cytoplasmic retention signal can be dominant over the NLS as is the case with cyclin B-cdc2 complexes (Pines and Hunter, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…Bcr-Abl also activates SAPK (Raitano et al, 1995). Significantly, both the JIP-1 inhibitor of SAPK and a dominant negative mutant of c-Jun block transforming activity of Bcr-Abl (Dickens et al, 1997;Raitano et al, 1995).These ®ndings have suggested that Bcr-Abl induces Jun-responsive promoters through a Ras-and SAPK-dependent pathway.…”
Section: Introductionmentioning
confidence: 94%
“…IB1/ JIP-1 can influence JNK signalling both positively and negatively, depending on the amounts of IB1/JIP-1 and its interacting kinases. [19][20][21] Our aim is to identify the critical features of the powerful protective action of the D-JNKI1 peptide and to examine JNK targets in excitotoxic neuronal death pathways. This can offer important clues to produce new inhibitors of excitotoxicity.…”
mentioning
confidence: 99%